2022
DOI: 10.1002/aoc.6709
|View full text |Cite
|
Sign up to set email alerts
|

Europhtal: An industrial cobalt phthalocyanine complex as the efficient catalyst for synthesis of thioamides by one‐pot reaction of mercaptans and amines

Abstract: The potential of industrial cobalt phthalocyanines in the synthesis of thioamides is reported. A mixture of an industrial sulfonated cobalt phthalocyanines known as Co[(SO3Na)2,3Pc] (Europhtal catalyst additive 8020) is introduced as an efficient catalyst capable of converting benzyl thiols to synthetically valuable thioamides by reaction with amines and DMSO. In this procedure, different primary and secondary amines also heterocyclic amines were successfully converted into benzothioamides in high yields. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Herein, we report an efficient and green micellar-assisted protocol for the transformations of thiols to disulfides and thioamides under mild conditions in water (Scheme 1, eqn (3)). Compared to similar studies 30 that have been reported (Scheme 1, eqn (1) and (2)), our system is milder, greener and cleaner with no transition metal required. Besides, both disulfides and thioamides can be obtained in moderate to excellent yields with a high level of tolerance of various functional groups.…”
Section: Introductionsupporting
confidence: 63%
“…Herein, we report an efficient and green micellar-assisted protocol for the transformations of thiols to disulfides and thioamides under mild conditions in water (Scheme 1, eqn (3)). Compared to similar studies 30 that have been reported (Scheme 1, eqn (1) and (2)), our system is milder, greener and cleaner with no transition metal required. Besides, both disulfides and thioamides can be obtained in moderate to excellent yields with a high level of tolerance of various functional groups.…”
Section: Introductionsupporting
confidence: 63%
“…It has to be noted that the SCoPc complex is often found in waste water since it is an industrial catalyst widely used in oil refineries and natural gas processing to remove mercaptans. , Therefore, the proposed synthesis strategy offers an additional advantage of shooting two hawks with one arrowenabling simultaneous preparation of hybrid catalysts and the elimination of SCoPc from wastewater (Figure b). Nevertheless, we would like to point out that other components may also exist in the real wastewater.…”
Section: Resultsmentioning
confidence: 99%